Improving students’ mathematics self-efficacy through problem based learning - Lisda Fitriana Masitoh; Harina Fitriyani (Universitas Malikussaleh, Aceh Utara, Indonesia, 2018)
One of the important affective factors for students in mathematics learning is self-efficacy. The students should have high mathematics self-efficacy. So, it can support the success of learning process. The facts that indicated the low of students’ mathematics self-efficacy, encouraging the efforts to improve self-efficacy through the improvement of the learning process. One of them is by applying the problem based learning approach. This research was a classroom action research by applying problem based learning approach to improve students’ mathematics self-efficacy. The classroom action research was done in two cycles. Each cycle consists of planning, action, observation, and reflection. The findings of this research revealed that the problem based learning approach could improve student’s mathematics self-efficacy. At the end of the first cycle, the students’ mathematics self-efficacy was still in the medium category and increased at the end of the second cycle, which students’ mathematics self-efficacy has been in high category.